Īmān, Islām, taqwā, kufr, shirk, and nifāq: Definitions, examples and impacts on human life - Hassan, Md Mahmudul (IIUC Studies, 2017)
The Holy Qur‟an encompasses the comprehensive code for mankind to live a rewarding life in this world, to rescue from the Jahannam and to enter the Jannah in the Hereafter. Īmān, Islām, taqwā, kufr, shirk, and nifāq are, the six significant terms, used in the Noble Qur‟an frequently. All of them represent the characteristics of human beings. The possessors of these characters will go to their eternal destination; the Jannah or Jahannam. The Jannah is the aftermath of īmān, Islam and taqwā. On the other hand, kufr, shirk, and nifāq lead to the Jahannam. This study intends to present the definitions and examples of these six terms according to the Qur‟anic statement, and then shed light on the impact of each character on human life quoting the evidence from the Holy Qur‟an and the Traditions of the Prophet Muhammad (PBUH). The possessors of these six remarkable terms are entitled successively as mu'min, muslim, muttaqī to be rewarded Jannah and kafīr, mushrik, and munāfiq to be punished in Jahannam. IIUC Studies Vol.14(2) December 2017: 85-98